Social costs and benefits of renewable electricity generation in Cyprus - Zachariadis, Theodoros; Hadjikyriakou, Costas; Kyriakides, Costas; Kanatzia, Aphrodite (My University, 2016)
Electricity produced by renewable sources increased at its fastest rate to date in 2014, accounting for almost half of the net additional power generating capacity worldwide. Within this international context, Cyprus is increasingly adopting renewable power generation too. This is particularly important since the country is highly dependent on imported petroleum products and electrically isolated, so that it needs adequate electricity supply to meet all national demand. This book presents an economic cost–benefit analysis of the deployment of renewable energy sources in Cyprus up to 2030, taking into account external costs and benefits from the diffusion of renewable electricity due to emissions of carbon dioxide and two air pollutants (nitrogen oxides and sulphur dioxide).
Keywords: Climate change; Economic growth; Energy demand; Energy security